Increased rat-borne zoonotic disease hazard in greener urban areas - Marieke P. de Cock; Ankje de Vries; Manoj Fonville; Helen J. Esser; Calvin Mehl; Rainer G. Ulrich; Maike Joeres; Donata Hoffmann; Tobias Eisenberg; Katja Schmidt; Marcel Hulst; Wim H.M. van der Poel; et al. (Science of The Total Environment, 2023)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Concentrations of dimethylaniline and other metabolites in milk and tissues of dairy cows treated with lidocaine - Ron L.A.P. Hoogenboom; Tina Zuidema; Martien Essers; Ad M. van Vuuren; Piet G. van Wikselaar; Jan C.H. van Eijkeren; Marcel J.B. Mengelers; Marco J. Zeilmaker; Astrid S. Bulder (Food Additives & Contaminants: Part A, 2015)

Dynamic oxygen mapping in the root zone by fluorescence dye imaging combined with neutron radiography - Nicole Rudolph; Hanna G. Esser; Andrea Carminati; Ahmad B. Moradi; André Hilger; Nikolay Kardjilov; Stefan Nagl; Sascha E. Oswald (Journal of Soils and Sediments, 2012)

Phylogenetic analysis of Puumala virus subtype Bavaria, characterization and diagnostic use of its recombinant nucleocapsid protein - Marc Mertens; Eveline Kindler; Petra Emmerich; Jutta Esser; Christiane Wagner-Wiening; Roman Wölfel; Rasa Petraityte-Burneikiene; Jonas Schmidt-Chanasit; Aurelija Zvirbliene; Martin H. Groschup; Gerhard Dobler; Martin Pfeffer; et al. (Virus Genes, 2011)

TRY – a global database of plant traits - J. KATTGE; S. DÍAZ; S. LAVOREL; I. C. PRENTICE; P. LEADLEY; G. BÖNISCH; E. GARNIER; M. WESTOBY; P. B. REICH; I. J. WRIGHT; J. H. C. CORNELISSEN; C. VIOLLE; et al. (Global Change Biology, 2011)
Plant traits – the morphological, anatomical, physiological, biochemical and phenological characteristics of plants and their organs – determine how primary producers respond to environmental factors, affect other trophic levels, influence ecosystem processes and services and provide a link from species richness to ecosystem functional diversity. Trait data thus represent the raw material for a wide range of research from evolutionary biology, community and functional ecology to biogeography. Here we present the global database initiative named TRY, which has united a wide range of the plant trait research community worldwide and gained an unprecedented buy‐in of trait data: so far 93 trait databases have been contributed. The data repository currently contains almost three million trait entries for 69 000 out of the world's 300 000 plant species, with a focus on 52 groups of traits characterizing the vegetative and regeneration stages of the plant life cycle, including growth, dispersal, establishment and persistence. A first data analysis shows that most plant traits are approximately log‐normally distributed, with widely differing ranges of variation across traits. Most trait variation is between species (interspecific), but significant intraspecific variation is also documented, up to 40% of the overall variation. Plant functional types (PFTs), as commonly used in vegetation models, capture a substantial fraction of the observed variation – but for several traits most variation occurs within PFTs, up to 75% of the overall variation. In the context of vegetation models these traits would better be represented by state variables rather than fixed parameter values. The improved availability of plant trait data in the unified global database is expected to support a paradigm shift from species to trait‐based ecology, offer new opportunities for synthetic plant trait research and enable a more realistic and empirically grounded representation of terrestrial vegetation in Earth system models.

Seroepidemiological study in a Puumala virus outbreak area in South-East Germany - Marc Mertens; Roman Wölfel; Katrin Ullrich; Kumiko Yoshimatsu; Jana Blumhardt; Ina Römer; Jutta Esser; Jonas Schmidt-Chanasit; Martin H. Groschup; Gerhard Dobler; Sandra S. Essbauer; Rainer G. Ulrich (Medical Microbiology and Immunology, 2009)

Adipose triglyceride lipase (ATGL) expression in human skeletal muscle is type I (oxidative) fiber specific - Johan W. E. Jocken; Egbert Smit; Gijs H. Goossens; Yvonne P. G. Essers; Marleen A. Baak; Marco Mensink; Wim H. M. Saris; Ellen E. Blaak (Histochemistry and Cell Biology, 2008)

Fluorescent benzofuran histamine H3 receptor antagonists with sub-nanomolar potency - M. Cowart; G. A. Gfesser; K. Bhatia; R. Esser; M. Sun; T. R. Miller; K. Krueger; D. Witte; T. A. Esbenshade; A. A. Hancock (Inflammation Research, 2006)

The mitochondrial IMP peptidase of yeast: functional analysis of domains and identification of Gut2 as a new natural substrate - K. Esser; P.-S. Jan; E. Pratje; G. Michaelis (Molecular Genetics and Genomics, 2004)

Mutagenic properties of 1,2,3,4-tetrahydronaphthaline-1-hydroperoxide, a model compound for organic peroxides in Diesel exhaust - S. Stock; G. Esser; D. Klockow; H. M. Bolt; G. H. Degen (Archives of Toxicology, 1998)